The balance between positive and negative affect in employee well‐being. (22nd November 2021) - Yoon, David J.; Bono, Joyce E.; Yang, Tao; Lee, KiYoung; Glomb, Theresa M.; Duffy, Michelle K.
Summary: We examine the effects of the balance between positive and negative affect experienced at work on well‐being outcomes. An extensive literature on affect balance suggests that it is not only positive affect (PA) and negative affect (NA) alone that affect well‐being; rather it is the balance between them that matters. We use experience sampling methods and polynomial regression to test the notion that daily PA and NA at work, along with their interactive and nonlinear effects, predict employee well‐being after work. In a sample of working adults, we find that affect balance—the dynamic interplay between daily PA and NA—at work was differentially associated with various indices of well‐being: PA, NA, and the interaction between them predicted physical and mental health. Affect balance at work also predicted life satisfaction, but only for those low on trait affect balance. Detailed examination of the joint effects of PA, NA, and the balance between them reveals that high PA at work is most important for life satisfaction, whereas both low NA and high PA are important for health. Low NA plays an especially important role in physical health.